A Proposed Matatag-Aligned Learning Activity Sheet for English Asynchronous Learning Modality - Enorme, Czarina; Punzalan, Randy (International Journal on Integrated Education, 2025)
Incorporating curriculum-relevant materials into asynchronous learning settings is key to enhancing grammar instruction, especially in the case of the MATATAG curriculum. This study examined the effectiveness of MATATAG-Aligned Learning Activity Sheets (LAS) in improving grammar competence among Grade 4 students of Santa Rosa Elementary School Central II. A quasi-experimental design was implemented, with one group utilizing improved MATATAG-Aligned Learning Activity Sheets (LAS) as the experimental group and another group utilizing conventional approaches as the control group. Grammar subject areas such as verbs, verb tenses, verb voices, adjectives, and complex sentences were emphasized. The post-test and pre-test scores were also compared, and Key Informant Interviews (KII) were conducted with English teachers. The results showed remarkable improvements in four grammar areas for students using the MATATAG-aligned Learning Activity Sheets (LAS). At the same time, both groups had a general decrease in scores during the post-test. Complex sentences were still the most challenging area, and there was no improvement. Teachers indicated more content, interactive teaching, and more formal teaching of complex concepts. The research finds that although MATATAG-aligned Learning Activity Sheets (LAS) can support learning grammar, their full potential is reached with instruction support, better design, and the use of technology. LAS can complement asynchronous English teaching and learning through better teacher training and resource creation.